Impacts of COVID-19 on Myanmar's chicken and egg sector, with implications for the sustainable development goals - Fang, Peixun; Belton, Ben; Zhang, Xiaobo; Ei Win, Hnin (Elsevier, 2021)
Chicken and eggs make important contributions to the food and nutrition security of low-income households in Myanmar, making it important to understand the impacts of COVID-19 on Myanmar's poultry sector.